Live learn love well : lessons from a life of progress not perfection - Lovewell, Emma (Ballantine Books, 2023)
"A memoir chronicling one woman's incredible journey to physical--and mental--fitness that will give readers an inside look at the hardships, heartbreaks, and trials she overcame to become a beloved Peloton instructor and an inspiration to people everywhere. Emma Lovewell is one of the star instructors for the fitness phenomenon Peloton, but her story is so much more than that--and it's a story she can't wait to share with her legions of fans. Emma's journey to success began with a simple realization: that change is inevitable, but growth is optional--and she chose to grow. In this book, Emma shares the moments in her life that inspired her to become the woman she is today--from growing up impoverished in the midst of Martha's Vineyard's affluence, to being one of the few students of color in her community, to struggling with her biracial identity, never feeling as though she fit in well enough with either the white community or the Asian American community, to moving to New York and striving to make a career in dance and fitness. And much in the same way that Emma is more than just a fitness instructor, she's learned that fitness is more than just a physical condition. Emma also shares the moments that her mental fortitude was even more important than her physical fortitude--touching on subjects like her mother's cancer diagnosis, past unhappy relationships, and finally understanding the importance of being kind to herself and surrounding herself with good friends. This is a book for anyone who feels stuck or overwhelmed by their current situation, who feels that there is too much they need to change to even get started. Emma's own journey, along with her easy-to-initiate tips, will give readers the confidence to know that even the smallest changes can have truly outsize impacts on their lives and happiness"--